2021
DOI: 10.1002/mp.15121
|View full text |Cite
|
Sign up to set email alerts
|

Stopping‐power ratios for electron beams used in total skin electron therapy

Abstract: Purpose The electron beams for total skin electron therapy (TSET) are often degraded by a scatter plate in addition to extended distances. For electron dosimetry, both the AAPM TG‐51 and IAEA TRS‐398 recommend the use of two formulas developed by Burns et al [Med. Phys. 23, 489–501 (1996)] to estimate the water‐to‐air stopping‐power ratios (SPRs). Both formulas are based on a fit to SPRs calculated for standard electron beams. This study aims to find: (1) if the formulas are applicable to beams used in TSET an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 40 publications
0
13
1
Order By: Relevance
“…Although for rotational technique similar mean dose coverages at the 1st 5 mm skin are seen, the dose coverages at the 2nd, and the 3rd 5 mm skin are significantly reduced for patient treated at the extended distance 500 cm. This is because the depth, R 50 , in water at which the absorbed dose falls to 50% of its maximum value, decreases approximately 1 mm for each additional 100 cm extended distances 17 . The thickness of the acrylic scatter plate needs to be reduced in order to achieve the same skin depth coverage.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although for rotational technique similar mean dose coverages at the 1st 5 mm skin are seen, the dose coverages at the 2nd, and the 3rd 5 mm skin are significantly reduced for patient treated at the extended distance 500 cm. This is because the depth, R 50 , in water at which the absorbed dose falls to 50% of its maximum value, decreases approximately 1 mm for each additional 100 cm extended distances 17 . The thickness of the acrylic scatter plate needs to be reduced in order to achieve the same skin depth coverage.…”
Section: Resultsmentioning
confidence: 99%
“…This is because the depth,R 50 ,in water at which the absorbed dose falls to 50% of its maximum value, decreases approximately 1 mm for each additional 100 cm extended distances. 17 The thickness of the acrylic scatter plate needs to be reduced in order to achieve the same skin depth coverage. Therefore, when patients are treated at an extended distance of 700 cm, there is no need to have an acrylic scatter plate in the patient treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14 There are very limited measured bremsstrahlung data for extended distances greater than 300 cm. Investigation by Chen et al 9 showed that bremsstrahlung dose is only ∼1% even at SSD > 500 cm for a 6 MeV beam from Varian 21EX-S and compared with the data of Das et al 12 The discrepancy was assumed to be caused by different 6 MeV beams generated from a Varian 21 EX-S and Saturne-I machines reported by Das et al 12 The results from recent Monte Carlo studies of 6 MeV beams by Ding et al 15,16 did not find a significant increase in bremsstrahlung doses even at extended distances of up to 700 cm. These results challenge the accuracy of the common belief that the bremsstrahlung dose is up to 5% at an extended distance of 500 cm.…”
Section: Introductionmentioning
confidence: 88%